Anesthesia in a patient with patent ductus arteriosus : case report (Revista Brasileira Multidisciplinar, 2026)
Patent ductus arteriosus (PDA) is the most common congenital heart defect in dogs, characterized by the failure to close a channel between the pulmonary artery and the aorta, which should close after birth. This study reports the anesthetic procedure of a dog with chronic PDA. The patient, an 8-year-old female Welsh Corgi weighing 17 kg, was treated at the Ulbra Veterinary Hospital complaining of a nodule in the right humerus. During auscultation, a grade V heart murmur was identified. The Doppler echocardiogram revealed the presence of retrograde flow in the pulmonary artery, with a communication between the aorta and the pulmonary artery, in the left-to-right direction, and these findings are compatible with PDA. Morphine (0.2 mg/kg), acepromazine (0.02 mg/kg) and ketamine (1 mg/kg) were administered intramuscularly as pre-anesthetic medication. Anesthesia was induced with remifentanil (5 mcg/kg/h), followed by propofol (2 mg/kg), both intravenously (IV). The patient was maintained in the anesthetic plane through continuous infusion of propofol, and remifentanil was maintained. In addition, perinodular blockade with lidocaine (0.1 ml/kg) was performed as an analgesic combination. During surgery, the patient presented bradycardia and hypotension, and scopolamine (0.2 mg/kg IV) and fluid loading were administered for stabilization. In the immediate postoperative period, dipyrone (25 mg/kg IV) and dexamethasone (0.5 mg/kg IV) were administered. The patient remained stable and was discharged on the same day. Prior patient assessment, personalized approach, continuous monitoring, and follow-up throughout the process were essential for the success of anesthesia.
Keywords: heart disease; congenital; adult; hemodynamics